PENGARUH WORK-LIFE BALANCE TERHADAP TURNOVER INTENTION DENGAN JOB SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi kasus pada Perawat di Rumah Sakit Umum Universitas Muhammadiyah) - Fauzan Septian; Sari Laelatul Qadriah; Mery Sukartini (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the effect of Work-life Balance on Turnover Intention with Job Satisfaction as an intervening variable among nurses at the Universitas Muhammadiyah Cirebon General Hospital. A quantitative approach was employed using a survey method through questionnaire distribution. The population in this study consisted of all nurses at the hospital, with a total sample of 109 respondents selected using a saturated sampling technique (census). Data analysis was conducted using the Structural Equation Modeling (SEM) approach with the assistance of SmartPLS 4 software. The results indicate that Work-life Balance has a significant effect on Job Satisfaction, and Job Satisfaction significantly influences Turnover Intention. Additionally, Work-life Balance also significantly affects Turnover Intention both directly and indirectly through Job Satisfaction as an intervening variable. These findings highlight the importance of managing Work-life Balance and enhancing Job Satisfaction as strategic efforts to reduce employees' intentions to leave the organization.